Preferred visual characteristics of pedestrian bridges in Tehran, Iran - Nejad, Nasim Sahraei (2014)
Due to rapid urban development, the presence of facilities for adapting to new situations has increased. Pedestrian bridges are such facilities in modern urban areas that provide such a linkage with a high level of safety for both pedestrian and cyclists and are as urban elements that can play an important role in create a new modern visual image for a city. However, the first and basic function of pedestrian bridges as an urban element has been their role in providing safety for the transportation system in urban areas, other roles have been attributed them during the time such as social and cultural roles. They thus have become an important part of a city’s public environment and one of their outstanding roles is their potential to beautify the urban areas. In fact, they could play a determinant role in depicting the aesthetic qualities of the urban landscape, especially when they meet certain critical principles. According to the literature, one of the most important factors that can play a determinant role in determining the aesthetic qualities of pedestrian bridges relates to the setting where these bridges are located. In fact, the most successful bridges should be designed in accordance with their surrounding environment. Therefore to help urban designers, bridge engineers, and planners improve the aesthetic qualities of pedestrian bridges in the urban landscape, base line data is needed regarding people’s perceptions of similar forms of pedestrian bridges in different urban landscape settings. Since urban environments are generally shaped by people’s preferences, perceptions, and attitudes toward their environment over time and also through studying their perceptions, people can indeed indicate what is important to them and what they need in this situation. Therefore such study can provide new insight into what these environments should be and help society better understand the ongoing relationship between human needs and the new urban areas. This input from people is essential to make the best decision for planning or design for the urban areas that serve the people. As such, this study attempts to provide new insights into how people view pedestrian bridges in an urban landscape and further reveal new details and information on people’s reactions to similar form of pedestrian bridges in these different urban landscapes. In summary, this study conducted a preference survey with 384 respondents in Tehran and entered the data into SPSS and then analyzed it through factor analysis and a content identifying method (CIM) and then a regression analysis. The results provide useful information first for considering the visual characteristics of the urban landscape where the pedestrian bridges are located; second, determining the potential factors that influence the aesthetic values of pedestrian bridges and the best predictors for public preferences, such as color, vegetation and natural features and finally provide implications for improving the visual aesthetic qualities of pedestrian bridges in urban areas of Tehran.